Category of time limit in administrative procedural law - Elena V. Beliakovich (Peoples’ Friendship University of Russia (RUDN University), 2021)
Administrative procedural law is full of numerous and varied procedural time limits which, as time-related categories, define the temporal boundaries of the administrative process and can act as an effective regulator of administrative procedural legal relations. The article examines the concept of time limit in administrative procedural law from the standpoint of integrativeness. It notes that the studied issue was not thoroughly elaborated in science, which appears to result from the young age of administrative procedural law as a separate branch. The research identifies substantial characteristics of the administrative procedural time limit. It reveals the temporal content of time limit in administrative procedural law. A conclusion is reached that the administrative procedural time limit results from the impact of temporal categories on the administrative procedural legal regulation when administrative cases are settled by a public administrative authority and a court. The administrative procedural time limit is recognised as a tool used for temporalizing the administrative process and aimed at ensuring the dynamism of administrative procedural activities through duration, speed, rhythm and cyclicity. The article identified the trend towards the legislative refinement of the administrative procedural time limits. In an integrative sense, the attributes inherent to the administrative procedural time limit reveal the versatility and rich inner content of the concept of time limit in administrative procedural law, which results from the legal synthesis of temporality and authoritative procedural activities of public administrative authorities and courts in settling administrative cases. The article proposed the definitions for the category of time limit in administrative procedural law both in a narrow and broad sense, as well as with an emphasis on the temporal side of the examined category.